Black Magic in Gray Titania: Noble‐Metal‐Free Photocatalytic H2 Evolution from Hydrogenated Anatase. Issue 1 (9th December 2016) - Liu, Ning; Zhou, Xuemei; Nguyen, Nhat Truong; Peters, Kristina; Zoller, Florian; Hwang, Imgon; Schneider, Christopher; Miehlich, Matthias E.; Freitag, Detlef; Meyer, Karsten; Fattakhova‐Rohlfing, Dina; Schmuki, Patrik
Abstract: 'Black' TiO2 —in the widest sense, TiO2 reduced by various treatments—has attracted tremendous scientific interest in recent years because of some outstanding properties; most remarkably in photocatalysis. While the material effects visible light absorption (the blacker, the better), black titania produced by high pressure hydrogenation was recently reported to show another highly interesting feature; noble‐metal‐free photocatalytic H2 generation. In a systematic investigation of high‐temperature hydrogen treatments of anatase nanoparticles, TEM, XRD, EPR, XPS, and photoelectrochemistry are used to characterize different degrees of surface hydrogenation, surface termination, electrical conductivity, and structural defects in the differently treated materials. The materials' intrinsic activity for photocatalytic hydrogen evolution is coupled neither with their visible light absorption behavior nor the formation of amorphous material, but rather must be ascribed to optimized and specific defect formation (gray is better than black). This finding is further confirmed by using a mesoporous anatase matrix as a hydrogenation precursor, which, after conversion to the gray state, even further enhances the overall photocatalytic hydrogen evolution activity. Abstract : Glad to be gray : This study shows that, in contrast to the general assumption, the optical absorption and the intrinsic photocatalytic activity of 'black' TiO2 are not the result of the same mechanistic origin and that for photocatalytic H2 evolution, a situation exists on optimized 'gray' titania whereby the type and concentration of cocatalytically active defects are optimized.